Relationship of Online Games with The Psychology of Children in Grades IV-VI at SD Inpres Sambung Jawa 2 Makassar: Hubungan Game Online dengan Psikologi Anak Kelas IV-VI di SD Inpres Sambung Jawa 2 Makassar - Herlianty; Evi Sri Dahrianti; Ferawati Taherong (Jurnal Midwifery, 2024)
The development of internet technology that is increasing so fast from time to time makes everything very easy to access for various ages including children. In connection with the use of the internet, online games are one of the applications that use internet access to play games. Online games are becoming a popular new thing because someone is no longer playing alone, but allows people to play with dozens of people at once from various locations. The purpose of this study was to determine online games with the psychology of children in grades IV-VI at SD Inpres Sambung Jawa 2 Makassar. This research method is quantitative with the research design used is analytic observation with a cross sectional approach. The population in this study were children who played online games at SD Inpres Sambung Jawa 1 Makassar as many as 76 students. The sample in this study is using probabiliti sampling with purposive sampling method of 76 students. The results of the study, through the statistical test used is a non-parametric statistical test using the Spearman Rank Correlation test, where the significant value or sig. (2-tailed) of 0.046 <0.05, which means there is a significant relationship between the relationship between online games and child psychology. The conclusion in this study is that there is a relationship between online games and child psychology at SD Inpres sambung Jawa 2 Makassar.